Angiosperm genome comparisons reveal early polyploidy in the monocot lineage - Tang, Haibao (National Academy of Sciences, 2009)
Although the timing and extent of a whole-genome duplication occurring in the common lineage of most modern cereals are clear, the existence or extent of more ancient genome duplications in cereals and perhaps other monocots has been hinted at, but remain unclear. We present evidence of additional duplication blocks of deeper hierarchy than the pancereal rho (ρ) duplication, covering at least 20% of the cereal transcriptome. These more ancient duplicated regions, herein called σ, are evident in both intragenomic and intergenomic analyses of rice and sorghum. Resolution of such ancient duplication events improves the understanding of the early evolutionary history of monocots and the origins and expansions of gene families. Comparisons of syntenic blocks reveal clear structural similarities in putatively homologous regions of monocots (rice) and eudicots (grapevine). Although the exact timing of the σ-duplication(s) is unclear because of uncertainties of the molecular clock assumption, our data suggest that it occurred early in the monocot lineage after its divergence from the eudicot clade.